Controle da população de morcegos hematófagos na região de Andradina, São Paulo - Santana, Ana Paula Lopes de [UNESP] (2012)
The control of the Desmodus rotundus bats populations is one of the measures included in the National Program of Herbivores Rabies Control of the Agriculture Ministry, which also includes vaccination of animals, epidemiological surveillance and health education. The methodology used for this control mainly includes the elimination of individuals or colonies of D. rotundus by the use of anticoagulant substances applied directly to sores produced by these animals in herbivores, or on the back of bats captured in shelters or in nets placed around the corrals. Besides this direct measure, the control of these bats populations also involves the registration and monitoring of shelters, the bites rate control in cattle and other herbivores in the properties and the send of specimens to the laboratory for the search of rabies virus. The aim of this study was to characterize the shelters and quantify the population of D. rotundus, in the region Andradina, São Paulo State, in the period from 2010 to 2012, in order to evaluate the effects of the actions adopted for control of bats, with the developing a critique of the method and propose actions to be forwarded to the National Program for Control of Herbivores Rabies of the Agriculture Ministry, hoping to improve knowledge of environmental impacts caused by the control, the impacts of the removal of bats for animal communities, and the transmission of rabies. Fifty shelters for bats registered by CDA and distributed in 12 municipalities were visited during the period from April to June 2010 and bats captured were treated with paste-based Warfarine. Thirty-one of them were re-inspected in September 2012. Most of the shelters, registered in the region, are artificial, corresponding to 92% and 97% of the total found in 2010 and 2012, respectively. Regarding the type of shelters, empty houses, sewers or tunnels under highways, tree holes, abandoned wells, bridges...